Dual action Smac mimetics–zinc chelators as pro-apoptotic antitumoral agents. Issue 19 (1st October 2016) - Manzoni, Leonardo; Gornati, Davide; Manzotti, Mattia; Cairati, Silvia; Bossi, Alberto; Arosio, Daniela; Lecis, Daniele; Seneci, Pierfausto
Graphical abstract: Abstract: Dual action compounds (DACs) based on 4-substituted aza-bicyclo[5.3.0]decane Smac mimetic scaffolds (ABDs) linked to a Zn 2+ -chelating moiety (DPA, o -hydroxy, m -allyl, N -acyl ( E )-phenylhydrazone) through their 10 position are reported and characterized. Their synthesis, their target affinity (XIAP BIR3, Zn 2+ ) in cell-free assays, their pro-apoptotic effects and cytotoxicity in tumor cells with varying sensitivity to Smac mimetics are described. The results are interpreted to evaluate the influence of Zn 2+ chelators on cell-free potency and on cellular permeability of DACs, and to propose novel avenues towards more potent antitumoral DACs based on Smac mimetics and Zn 2+ chelation.